Comparison of Clinical Outcomes and Complications Between Endoscopic and Minimally Invasive Transforaminal Lumbar Interbody Fusion for Lumbar Degenerative Diseases: A Systematic Review and Meta-analysis. Issue 5 (June 2023) - Guo, Haiwei; Song, Yuke; Weng, Rui; Tian, Han; Yuan, Jiayao; Li, Ying
Study design: Systematic review and meta-analysis. Objective: Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) is a classic surgical procedure for the treatment of lumbar degenerative diseases (LDD). With the development of endoscopic technology, endoscopic transforaminal lumbar interbody fusion (Endo-TLIF) can also achieve adequate decompression and interbody fusion. However, whether Endo-TLIF is superior to MIS-TLIF has not been adequately studied. In this systematic review and meta-analysis, we aimed to evaluate the treatment difference between Endo-TLIF vs MIS-TLIF. Methods: We conducted a systematic review and meta-analysis of the studies to compare the clinical outcomes and complications associated with Endo-TLIF vs. MIS-TLIF for the treatment of LDD. A literature search was conducted using the PubMed, Embase, Cochrane Library and Scopus databases for studies published up to April 1, 2022. Both retrospective and prospective studies that compared between Endo-TLIF and MIS-TLIF were included. Results: A total of 8 studies involving 581 patients were finally included in this meta-analysis. Endo-TLIF significantly prolonged the operation time, but reduced the blood loss amount and length of hospital stay. Moreover, Endo-TLIF was superior to MIS-TLIF on relief of back pain and functional recovery in the early postoperative period. However, there were no significantly differences in long-term clinical outcomes, fusion rate and incidence of complications between Endo-TLIF and MIS-TLIF. Conclusions: Endo-TLIF was similar to MIS-TLIF in the long-term clinical outcomes, fusion and complication rates. Endo-TLIF prolongs the operation time, but shortens the length of hospital stay, and has the advantages of less surgical trauma, less blood loss, faster recovery, and early postoperative back pain relief.